2022
DOI: 10.1155/2022/2290644
|View full text |Cite|
|
Sign up to set email alerts
|

Operating Room Planning for Emergency Surgery: Optimization in Multiobjective Modeling and Management from the Latest Developments in Computational Intelligence Techniques

Abstract: This study presents an optimization approach for scheduling the operation room for emergency surgeries, considering the priority of surgeries. This optimization model aims to minimize the costs associated with elective and emergency surgeries and maximize the number of scheduled surgeries. In this study, surgeon assistants to perform each surgery are considered in order to achieve the goals. Since the time of each surgery varies according to the conditions of the patient, this parameter is considered as an unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Equation (7) indicates that elective patients will only be served once. Equation (8) supposes that emergency patients follow Poisson distribution 29,30 . Equation (9) indicates that the number of emergency patients admitted does not exceed the maximum number in the Poisson distribution.…”
Section: Allocation Model Of the First Stagementioning
confidence: 99%
“…Equation (7) indicates that elective patients will only be served once. Equation (8) supposes that emergency patients follow Poisson distribution 29,30 . Equation (9) indicates that the number of emergency patients admitted does not exceed the maximum number in the Poisson distribution.…”
Section: Allocation Model Of the First Stagementioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%